2021
DOI: 10.1002/aenm.202101126
|View full text |Cite
|
Sign up to set email alerts
|

Fast Charging of Lithium‐Ion Batteries: A Review of Materials Aspects

Abstract: Fast charging is considered to be a key requirement for widespread economic success of electric vehicles. Current lithium‐ion batteries (LIBs) offer high energy density enabling sufficient driving range, but take considerably longer to recharge than traditional vehicles. Multiple properties of the applied anode, cathode, and electrolyte materials influence the fast‐charging ability of a battery cell. In this review, the physicochemical basics of different material combinations are considered in detail, identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
348
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 545 publications
(395 citation statements)
references
References 365 publications
0
348
0
2
Order By: Relevance
“…For increasing charge rates (right hand side of Figure 3b), both cell designs show a less stable rate capability compared to increasing discharge rates, as can be expected due to the limited kinetics for lithiation of the graphite anodes [15]. Considering the charge capacities at 0.1C as 100%, the capacity at 3C decreases to 64.6% in the case of the welded tabs and to 58.2% in the case of the foil tabs.…”
Section: Resultsmentioning
confidence: 61%
“…For increasing charge rates (right hand side of Figure 3b), both cell designs show a less stable rate capability compared to increasing discharge rates, as can be expected due to the limited kinetics for lithiation of the graphite anodes [15]. Considering the charge capacities at 0.1C as 100%, the capacity at 3C decreases to 64.6% in the case of the welded tabs and to 58.2% in the case of the foil tabs.…”
Section: Resultsmentioning
confidence: 61%
“…It can be observed that semicircles in higher frequency is smallest for Mo 2 C/C/rGO followed by Mo 2 C/rGO, Mo 2 C/C and Mo 2 C. This indicates that Mo 2 C/C/rGO experience least resistance compared to Mo 2 C/rGO, Mo 2 C/C and Mo 2 C. The lowest charge transfer resistance ( R ct ) of Mo 2 C/C/rGO suggests that Faradic reaction is fastest in this samples than others. This is due to the fact that both amorphous carbon and rGO present in the composite act as an efficient charge carrier and smoothen the progress of charge transfer at the interface [52,53] . The resistances due to SEI layer and charge‐transfer process are found to be higher in the samples after 100 th cycles (Table 1).…”
Section: Resultsmentioning
confidence: 94%
“…It can be observed that semicircles in higher frequency is smallest for Mo 2 C/C/rGO followed by Mo ChemElectroChem composite act as an efficient charge carrier and smoothen the progress of charge transfer at the interface. [52,53] The resistances due to SEI layer and charge-transfer process are found to be higher in the samples after 100 th cycles (Table 1). Generally, the impedance increases with an increase in cycle number which could be attributed to increase in resistance of broken surface structure of electrodes, formation of defects etc.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…Plating lithium on the negative electrode can become thermodynamically and kinetically favorable at large current densities and low temperatures. [95,96] It is important to note the heterogeneity of this phenomenon in porous electrodes [97] and its coupling to inhomogeneous SEI growth deserves future attention. A further challenge, especially for lithium metal electrodes, is the tendency of electrochemically deposited lithium to form structures with high surface areas, e.g., nano-scale whiskers and micro-scale dendrites, [98] which entails a continued formation of fresh SEI and lithium loss.…”
Section: Understanding the Sei From A Multi-scale And Multi-domain Ap...mentioning
confidence: 99%